ENVIRONMENT SENSITIVITY MAPS OF LAND DEGRADATION AND DESRTIFICATION USING MEDULAS MODEL AND REMOTE SENSING IN SHIRQAT CITY/IRAQ - & Hussien, Khalaf (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This research of aims to study environment sensitivity of desertification and land degradation using MEDULAS project and remote sensing in AL-Shirqat City/Salahadin/Iraq. A 10 soil pedons were chosen from study area depending on difference in soil preperties, landuse and causes of desertification and degradation as (Salinity, Erosion, Gypsum and vegetation cover). Soil profile description, soil samples and GPS were conducted. The physical (texture) and chemical (CaCO3, CaSO4.2H2O, O.M, EC and pH) properties were determined. The Soil were classified as Torrifluvents in the (P1, P2, P3), Torripsamments in the (P5 and P7), Calcigypsids in the (P6, P8 and P10) and Calcids in the P4. The landsat 8 image at 20sep. 2019 and 19 sep. 2013 were aquired in the spectral indices calculate and spatial maps by using ERDAS 15 and GIS 10.2. The result show contrast in soil propreties as sand, clay, soil gypsum, CaCO3, OM and EC that reflect on Soil Quality Index (SQI) which were (60)% poor quality  and (40)% moderate quality degradation. While (19.10) % that moderate quality and 80.90% that poor quality for Vegetation Quality Index.  The results show that 0.1% of the study area is classiﬁed as C1; 25.35%  as C2; 74.55% of the areas as C3. The spectral indices as LAI, SI5, OSAVI were approporiate for monitor of desertification and degradation in study area. Add, spatial change in the spectral indices as NDVI and LAI. The results shown that MEDALUS model is a important model in the areas disposed to desertification and degradation.